Associação da condição socioeconômica na qualidade do sono de pessoas idosas que vivem em áreas de alta vulnerabilidade social - Guiesi, Pedro Henrique Machado (Universidade Federal de São Carlos, 2025)
The literature indicates that socioeconomic status, as well as aging, can lead to changes in sleep patterns. However, studies on income and sleep quality focused on community-dwelling elderly individuals have proven to be scarce. Thus, the present study aims to analyze the association between socioeconomic status and sleep quality of elderly individuals living in areas of high social vulnerability. This is a quantitative, descriptive, and cross-sectional study. The sample consisted of elderly individuals registered in Family Health Units located in areas of high social vulnerability in the city of São Carlos, São Paulo. Data collection was performed through interviews with the application of a characterization questionnaire developed for the study together with the Pittsburgh Sleep Quality Index. The data obtained were entered into a database in the Statistical Package for Social Sciences for Windows program for descriptive and comparative statistical analyses (Pearson's Chi-Square Test, Fisher's Exact Test, and Kruskal-Wallis Test). A total of 110 elderly individuals were interviewed and divided into three comparative groups based on family income tertiles. The sociodemographic profile of the sample was young, i.e., the average age was less than 70 years. The level of education was low. Individual and family incomes were less than 1.5 and 2.5 minimum wages, respectively. The elderly were predominantly female (55.5%), married (94.5%), brown (46.4%), retired (79.1%) and with a perception of insufficient income to meet daily demands (56.4%). The results indicate that, in the group of elderly people with high income, the proportion of individuals with very good subjective sleep quality was significantly higher when compared to the other groups. In agreement, the overall raw score related to poor sleep quality was significantly higher among elderly people with low income. It is concluded that socioeconomic status has negative implications on the sleep quality of elderly people living in areas of high social vulnerability.
Association of socioeconomic status on the sleep quality of elderly people living in areas of high social vulnerability
Keywords: Sono; Renda; Pessoa Idosa; Vulnerabilidade social; Sleep; Income; Elderly; Social vulnerability; CIENCIAS DA SAUDE::SAUDE COLETIVA